Modeling and frequency characteristic analysis of DSOGI-PLL in dq reference frame - Yongxin Zhang (Elsevier, 2021)
Dual second-order generalized integrator phase-locked loop (DSOGI-PLL) is widely used in grid-connected system for grid synchronization because of its simple implementation and good filtering capability. However, the frequency characteristics of DSOGI-PLL affect the impedance modeling of the system, which in turn affect the impedance-based stability analysis. In order to improve the accuracy of system modeling, in this paper, the equivalent transfer function of positive-sequence calculator (PSC) block constructed in αβreference frame in DSOGI-PLL is presented in dq reference frame, where the relationship between DSOGI-PLL and traditional synchronous reference frame PLL (SRF-PLL) small-signal model is investigated. Then, based on the established model, DSOGI-PLL and SRF-PLL are compared from the tracking characteristics and robustness characteristics. It is further demonstrated that DSOGI-PLL is able to improve the robustness performance of PLL while maintaining the same tracking performance as SRF-PLL. Finally, simulation results are presented to validate the established model and frequency characteristic analysis.